Evaluating and Managing Electronic Commerce and Outsourcing Projects in Hospitals - Lin, Chad; Jalleh, G.; Huang, Y. (2016)
Despite the huge popularity of outsourcing in electronic commerce/IT in the past two decades, many hospitals have failed to realize the expected benefits from their outsourcing projects. Not surprisingly, the management of electronic commerce/IT outsourcing contracts has become one of the top management issues for hospitals executives in recent years. Hence, the purpose of this study was to provide an over - view of outsourcing in electronic commerce/IT investment evaluation and benefits realization processes and practices in Australian and Taiwanese hospitals. Inherent in this study was the opportunity to compare such practices between a developed economy (Australia) and a newly industrialized economy (Taiwan). Several key electronic commerce/IT investment evaluation and outsourcing issues and challenges faced by Australian and Taiwanese hospitals will be presented. The results will assist hospital executives to develop their own approaches and strategies to better manage the opportunities and threats that exist in undertaking electronic commerce/IT outsourcing projects in Australian and Taiwanese hospitals.